Working on waste: beyond ahistorical chronicles and false dichotomies in circular economy narratives. (3rd April 2022) - Rainnie, Al; Herod, Andrew
ABSTRACT: In this article we look at waste and working on waste. In particular, we set out a case against analyses that see working on waste as somehow outside of capitalism, an informal system quite separate from, and other to, formal work. To do so, we first outline the nature of contemporary waste production. We then put forward three caveats to the emerging orthodoxy on waste and waste work, doing so through presenting a brief history of waste work in Victorian Britain, through an exploration of how tracing the movement of value (in the Marxian sense of congealed labour) from waste to new commodities (and, often, back again) problematises views that see waste work as detached from capitalist labour processes, and through a questioning of what waste work means for the oft-made 'formal/informal' division of work. Specifically, we argue that working on waste is complex and even at its most basic it remains part of a continuum of working practices, regulations, and relations, rather than being hermetically sealed off from 'formal' employment.